Effects of Postpartum Family Planning Counselling on Contraceptives Knowledge, Attitude and Intention Among Women Attending a General Hospital in The Gambia: A Randomized Controlled Trial - Sey-Sawo J; Adeyemo FO; Okojie OH (Dove Medical Press, 2023)
Jainaba Sey-Sawo,1 Florence O Adeyemo,2 Obehi H Okojie3 1Department of Nursing and Reproductive Health, University of The Gambia, Serekunda, The Gambia; 2Department of Nursing, University of Benin, Benin, Edo State, Nigeria; 3Department of Community Health, University of Benin, Benin, Edo State, NigeriaCorrespondence: Jainaba Sey-Sawo, School of Medicine and Allied Health Sciences, University of The Gambia, P. O. Box 1646, Serekunda, The Gambia, Tel +220 3650105, Email jsey@utg.edu.gmPurpose: This study aimed to evaluate the effectiveness of PPFP counselling on contraceptives knowledge, attitudes and intention among women attending a general hospital in The Gambia.Materials and Methods: A quasi-experimental design with an intervention and comparison group was used. The intervention was PPFP counselling using the GATHER approach. A sample size of 674 participants was determined by a formula for comparison between the two groups. The questionnaire was developed based on a literature review and was pre-tested on 10% of the total study sample size (68). A reliability of 0.731 was obtained. A systematic random sampling method was employed to select study participants who met the inclusion criteria. Data were collected during face-to-face interviews in local languages with a 100% response rate at baseline and 96% at post-test. Data were analysed using the SPSS version 21.00 and the statistical analysis included both descriptive and inferential methods. An ethical approval was obtained from the Research and Ethics Committee, School of Basic Medical Sciences, College of Medicine, University of Benin (CMS/REC/2017/017) and the Gambia Government/Medical Research Council Laboratories Joint Ethics Committee (R017016Av1.1).Results: Baseline respondents' socio-demographic characteristics revealed that the two groups had similar characteristics. A statistically significant difference existed on knowledge, attitude, and intention to use contraceptive methods between the intervention and comparison groups at post-intervention (p< 0.05) while no significant difference was observed at baseline. Significant gains were achieved in the intervention group in terms of knowledge, attitude, and intention post-intervention.Conclusion: PPFP counselling during the postpartum period and before the discharge of women from the hospital may improve knowledge, attitude and intention to use contraceptives and, therefore, increase the likelihood of contraceptive uptake and thus prevent unwanted and closely spaced pregnancies.Keywords: interventional, post-delivery, research, The Gambia